The importance of Management Control Systems - KARAOULANIS, ANDREAS (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
This paper is trying to give us a short introduction to MCSs(Management Control systems), their definition, categories, implementation, evaluation and design in contemporary companies, as well as to underline their importance for the overall eurythmic companys function.